2020
DOI: 10.3390/clockssleep2040033
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression in Brain and Liver Tissue of Wistar Rats after Rapid Eye Movement Sleep Deprivation

Abstract: Sleep is essential for the survival of most living beings. Numerous researchers have identified a series of genes that are thought to regulate “sleep-state” or the “deprived state”. As sleep has a significant effect on physiology, we believe that lack of total sleep, or particularly rapid eye movement (REM) sleep, for a prolonged period would have a profound impact on various body tissues. Therefore, using the microarray method, we sought to determine which genes and processes are affected in the brain and liv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 192 publications
0
6
0
Order By: Relevance
“…The ZNF184 encodes a Kruppel C2H2-type zinc-finger protein family member, which participates in gene expression regulation. One study found that REM sleep deprivation in rats induced significant ZNF184 down-regulation in the brain [ 46 ]. The effects of this mutation on other features of PD are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The ZNF184 encodes a Kruppel C2H2-type zinc-finger protein family member, which participates in gene expression regulation. One study found that REM sleep deprivation in rats induced significant ZNF184 down-regulation in the brain [ 46 ]. The effects of this mutation on other features of PD are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous reports have shown a close relation between sleep and sleep deprivation and ER stress and UPR [ 43 , 44 , 45 ], most of the basic research has been done in brain regions such as the hypothalamus and cerebral cortex. Pandey et al [ 20 ] evaluated gene transcript expression in the brain and liver of rats treated with 9 days of REM sleep deprivation. In their report, 652 genes were altered in brain and 426 genes were affected in the liver, but only 23 genes had changes in common (10 opposite, 13 in the same directions) across the brain and liver tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that biological molecular changes induced by sleep and sleep deprivation may be consistent between the central and peripheral regions, while others may not. Indeed, Pandey et al [ 20 ] concluded that the brain functions related to synaptic potentiation, learning and memory, oxidative stress, and circadian rhythms were more vulnerable to REM sleep deprivation. On the other hand, REM sleep loss strongly affected protein synthesis, stress balance, and detoxification in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study revealed that, in the cortex and hypothalamus of sleep-deprived mice, 2499 genes changed their expression due to sleep deprivation [27]. Similar variations were observed in the rat liver, where 426 genes were modified [28]. On the other hand, analysis of the blood transcriptome is a reference tool with which to relate gene expression with other systems in the organism [29].…”
Section: Sleep As a Modulator Of Circadian Rhythmsmentioning
confidence: 95%